Palmitoylethanolamide Exerts Antiproliferative Effect and Downregulates VEGF Signaling in Caco‐2 Human Colon Carcinoma Cell Line Through a Selective PPAR‐α‐Dependent Inhibition of Akt/mTOR Pathway. (1st March 2016) - Sarnelli, Giovanni; Gigli, Stefano; Capoccia, Elena; Iuvone, Teresa; Cirillo, Carla; Seguella, Luisa; Nobile, Nicola; D'Alessandro, Alessandra; Pesce, Marcella; Steardo, Luca; Cuomo, Rosario; Esposito, Giuseppe
Abstract : Palmitoylethanolamide (PEA) is a nutraceutical compound that has been demonstrated to improve intestinal inflammation. We aimed at evaluating its antiproliferative and antiangiogenic effects in human colon adenocarcinoma Caco‐2 cell line. Caco‐2 cells were treated with increasing concentrations of PEA (0.001, 0.01 and 0.1 μM) in the presence of peroxisome proliferator‐activated receptor‐a (PPAR‐α) or PPAR‐γ antagonists. Cell proliferation was evaluated by performing a MTT assay. Vascular endothelial growth factor (VEGF) release was estimated by ELISA, while the expression of VEGF receptor and the activation of the Akt/mammalian target of rapamycin (mTOR) pathway were evaluated by western blot analysis. PEA caused a significant and concentration‐dependent decrease of Caco‐2 cell proliferation at 48 h. PEA administration significantly reduced in a concentration‐dependent manner VEGF secretion and VEGF receptor expression. Inhibition of Akt phosphorylation and a downstream decrease of phospho‐mTOR and of p‐p70S6K were observed as compared with untreated cells. PPAR‐α, but not PPAR‐γ antagonist, reverted all effects of PEA. PEA is able to decrease cell proliferation and angiogenesis. The antiangiogenic effect of PEA depends on the specific inhibition of the AkT/mTOR axis, through the activation of PPAR‐α pathway. If supported by in vivo models, our data pave the way to PEA co‐administration to the current chemotherapeutic regimens for colon carcinoma. Copyright © 2016 John Wiley & Sons, Ltd.